2007
DOI: 10.1007/s00586-006-0276-8
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal muscle control in people with osteoporotic vertebral fracture

Abstract: The high risk of sustaining subsequent vertebral fractures after an initial fracture cannot be explained solely by low bone mass. Extra-osseous factors, such as neuromuscular characteristics may help to explain this clinical dilemma. Elderly women with (n = 11) and without (n = 14) osteoporotic vertebral fractures performed rapid shoulder flexion to perturb the trunk while standing on a flat and short base. Neuromuscular postural responses of the paraspinal muscles at T6 and T12, and deep lumbar multifidus at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
(50 reference statements)
1
13
1
4
Order By: Relevance
“…A study by Sinaki and colleagues suggested that stronger back muscles may help in reducing vertebral fracture [39]. Another study showed that elderly women with vertebral fracture had better paraspinal muscle control than those with vertebral fracture [40]. In our study, greater total paraspinal muscle volume was weakly associated with higher non-spine fractures but this was only significant after adjusting for grip strength, fracture history and diabetes.…”
Section: Discussioncontrasting
confidence: 45%
“…A study by Sinaki and colleagues suggested that stronger back muscles may help in reducing vertebral fracture [39]. Another study showed that elderly women with vertebral fracture had better paraspinal muscle control than those with vertebral fracture [40]. In our study, greater total paraspinal muscle volume was weakly associated with higher non-spine fractures but this was only significant after adjusting for grip strength, fracture history and diabetes.…”
Section: Discussioncontrasting
confidence: 45%
“…The lowest mean srBMD was observed in the anterior subregion (ROI 4), a result consistent with previous ex vivo histomorphometry, QCT, and DXA studies [36–40, 42, 43] and the highest was in the posterior subregion (ROI 2). This distribution pattern is probably explained by a combination of a higher cortical bone component in the posterior subregion compared to the anterior subregion and a result of changes in vertebral loading profiles, in particular intervertebral disc degeneration and changes in lumbar spine posture [21, 57]. When disc degeneration occurs, force loading increases on the neural arch, hence decreasing loading on the anterior region and causing regional demineralisation [5759].…”
Section: Discussionmentioning
confidence: 99%
“…Vertebral fractures frequently occur spontaneously or from minor trauma [18] and are associated with morbidity including decreased physical function (e.g., balance and muscle function), loss of height, compromised pulmonary capacity, increased thoracic kyphosis, and acute and chronic back pain [6, 15, 1721]. These sequelae become more significant with increasing numbers of vertebral fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebral fractures were associated with low muscle strength in both sexes and lower functional reach of arms in women, not men . In women, they were associated with abnormal electromyographic activity of trunk and paraspinal muscles . However, grip strength and major fragility fractures are associated with high mortality .…”
Section: Discussionmentioning
confidence: 97%
“…15,16,67,68 In women, they were associated with abnormal electromyographic activity of trunk and paraspinal muscles. 69,70 However, grip strength and major fragility fractures are associated with high mortality. 71,72 Thus, the association between fractures and low grip strength may reflect residual confounding related to factors impairing health and bone strength and not accounted for in the model, e.g.…”
Section: Discussionmentioning
confidence: 99%